Evaluation of an Injection Training and Certification Program for Pharmacy Students - Banh, Hoan Linh (American Journal of Pharmaceutical Education, 2014)
Objective. To evaluate an injection training and certification program for third-year (P3) pharmacy students, and to measure the impact of students’ administration of immunizations at an influenza clinic on their knowledge, skills, and competence in immunization. Design. A repeated measures design was used to assess students’ injection skills across the injection training and certification program and the influenza clinic. A repeated measures design was also used to evaluate students’ self-reported knowledge, experience, and confidence. Assessment. Postcertification and during influenza clinic comparisons showed significant improvement in students’ knowledge, experience, and confidence after taking part in the influenza clinic. University staff members and students indicated in a survey that they were satisfied with the clinic services provided by pharmacy students. Conclusion. The injection training and certification program and the university influenza clinic were effective in enhancing and fostering student skills development.